2022
DOI: 10.1371/journal.pone.0260222
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high platelet turnover on the platelet transcriptome: Results from platelet RNA-sequencing in patients with sepsis

Abstract: Background Sepsis is associated with high platelet turnover and elevated levels of immature platelets. Changes in the platelet transcriptome and the specific impact of immature platelets on the platelet transcriptome remain unclear. Thus, this study sought to address whether and how elevated levels of immature platelets affect the platelet transcriptome in patients with sepsis. Methods Blood samples were obtained from patients with sepsis requiring vasopressor therapy (n = 8) and from a control group of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…21 Moreover, RNAseq of human and murine platelets showed that the platelet transcriptional and translational landscapes are significantly altered in sepsis, and that upregulation of ITGA2B is associated with higher mortality 22 providing novel evidence that upregulation of protein synthetic events in platelets may play a pathogenic role in sepsis. A recent study 23 confirmed the differential expression of several genes in platelets from sepsis patients compared to controls and showed that upregulated genes were mostly related to catabolic processes and protein translation. The Authors also showed that patients with sepsis have increased levels of immature platelets and a less degraded platelet transcriptome, as indicated by decreased levels of circRNAs.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…21 Moreover, RNAseq of human and murine platelets showed that the platelet transcriptional and translational landscapes are significantly altered in sepsis, and that upregulation of ITGA2B is associated with higher mortality 22 providing novel evidence that upregulation of protein synthetic events in platelets may play a pathogenic role in sepsis. A recent study 23 confirmed the differential expression of several genes in platelets from sepsis patients compared to controls and showed that upregulated genes were mostly related to catabolic processes and protein translation. The Authors also showed that patients with sepsis have increased levels of immature platelets and a less degraded platelet transcriptome, as indicated by decreased levels of circRNAs.…”
mentioning
confidence: 78%
“…The biological implications of the increased platelet turnover remain unclear, however this study first suggested that increased protein translation is a characteristic mechanism of systemic inflammation. 23 Intriguingly, there is a large overlap of the platelet transcriptome changes observed either in sepsis or in COVID-19. [22][23][24] Distinctive changes in the gene-expression profile of circulating platelets of COVID-19 patients have been shown involving the pathways associated with protein ubiquitination, antigen presentation, and mitochondrial dysfunction, 24 suggesting a drastic change in the redox balance and in platelet metabolism leading to platelet activation and to the high thrombotic risk of COVID-19 patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, since MPV in the early stages of infection did not differ, multivariate logistic regression analysis showed that the MVP/PLT ratio is not an early predictor of severe neonatal infection; this result is inconsistent with the findings of related studies. 22 , 23 This change may be due to the following reasons: (1) PLT levels increase in the early stage of infection, while the number of immature platelets in the blood increases in the recovery stage; an increase in MPV levels compensates for the adverse consequences of decreased PLT; 24 (2) relevant studies do not indicate clearly whether data were drawn from the early or the recovery stage of infection. Therefore, the increase in MPV levels may derive from the recovery stage of infection rather than the early stage, which necessitates further research and discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Respecto a los otros parámetros plaquetarios derivados de los autoanalizadores de hematología y la infección por SARS-CoV-2, con relación al volumen medio plaquetario (VMP por la sigla en inglés Mean Platelet Volume) y el ancho de distribución de las plaquetas (PDW por la sigla en inglés Platelet Distribution Width) no hay información suficiente para postularlos como predictores en la infección por SARS-CoV-2. Las plaquetas reticuladas, también conocidas como fracción de plaquetas inmaduras o reticuloplaquetas, son plaquetas jóvenes, de 1 a 2 días, que se caracterizan por una alto contenido de ARN (76), lo que en la práctica refleja un aumento de la trombopoyesis y en la clínica se correlaciona con condiciones inflamatorias activas y severas (77) y puede servir como un predictor de progresión a un estado severo de la enfermedad y desenlaces fatales en pacientes críticos con COVID-19 (78)(79)(80)(81), íntimamente relacionadas con aumento del riesgo cardiovascular (79) y desenlace fatal cuando el paciente tiene una sepsis sobreagregada (81).…”
Section: Alteraciones En El Trombogramaunclassified